Smoking is a risk factor for postoperative ileus after radical resection in male patients. Issue 42 (22nd October 2021) - Wang, Jiangling; Guo, Wenjing; Cui, Xiaoying; Shen, Yajian; Guo, Ye; Cai, Yunfang; Liu, Xinyi; Fang, Man; Gu, Bin; Yuan, Junbo; Xie, Yuyizi; Xie, Kangjie; et al.
Abstract : Abstract: Most smokers are males, and smoking has been indicated as a risk factor for many cancers as well as postoperative complications after cancer surgery. However, little is known about whether smoking is a risk factor for postoperative ileus (POI) after radical rectal cancer resection in males. The aim of this study was to assess whether smoking is a risk factor for POI after radical resection in male rectal cancer patients. Data of 1486 patients who underwent radical resection for rectal cancer were extracted from the clinical medical system in our hospital and were statistically analyzed. POI was defined as nausea, vomiting or pain, failure to have bowel function for more than 4 days postoperatively, and absence of a mechanical bowel obstruction. The rate of POI was 12.79%. Univariate analysis showed that patients in the POI group were more likely to have a history of smoking and drinking and receive intraperitoneal chemotherapy and had a larger intraperitoneal chemotherapy dosage. In the multivariable analysis, smoking remained significantly associated with a higher incidence of POI (OR 2.238, 95% CI [1.545–3.240], P = .000). The results also showed that patients who received postoperative patient-controlled intravenous analgesia had a lower incidence of POI. Male patients with a history of smoking who undergo elective radical resection for rectal cancer have an increased risk for POI complications.